100 questions & answers about schizophrenia : painful minds - DeLisi, Lynn E. (Sudbury, Mass. : Jones and Bartlett Publishers, 2011)
Overview: Schizophrenia is a chronic, severe mental illness that can be devastating for patients and their loved ones. Whether you are a newly diagnosed patient or a relative of someone suffering from this condition, this book offers help. 100 Questions & Answers About Schizophrenia: Painful Minds, Second Edition, provides authoritative, practical answers to your questions about symptoms, diagnosis, treatment options, sources of support, and much more. Expert psychiatrist Dr. Lynn E. DeLisi has updated her book with new facts, statistics, and helpful information that many patients and their families seek. This book is an invaluable resource for anyone coping with the physical, mental, and emotional turmoil of schizophrenia
Part 8: Suicidal Behavior and Schizophrenia -- Questions 81-82 discuss how to best recognize someone at high risk for suicidal behaviors and prevent this tragic outcome: -- 81: What are the signs of suicidal thoughts in schizophrenia? -- 82: What can be done to prevent suicide attempts? -- Part 9: Issues For Women: -- Questions 83-87 review specific issues unique to female patients with schizophrenia: -- 83: Is schizophrenia different in women? -- 84: Should patients who are pregnant take medication for schizophrenia? -- 85: What is the risk of a postpartum relapse? -- 86: What about breast-feeding? -- 87: Can estrogen for birth control help suppress symptoms? -- Part 10: Homeless And Schizophrenia: -- Questions 88-90 discuss the connections between homelessness and mental illness: -- 88: How prevalent is schizophrenia among the homeless? -- 89: What causes homelessness? -- 90: Can homeless people be forced into shelters and hospitals? -- Part 11: Living With Schizophrenia -- Questions 91-94 provide information on the quality of daily life of someone with schizophrenia: -- 91: What are the origins of the stigma attached to having schizophrenia? -- 92: Can a person with schizophrenia be professionally creative? -- 93: Should I adopt a baby whose birth parent had schizophrenia? -- 94: Should a person with schizophrenia drive a car? -- Part 12: Ethical Issues: -- Questions 95-100 examine ethical issues relevant to someone who has schizophrenia: -- 95: What does "involuntary" hospital commitment involve? -- 96: What is the legal insanity defense? -- 97: Have there been abuses of the insanity defense? -- 98: Do patients with schizophrenia have the capacity to give informed consent for research and other procedures? -- 99: Can genetic information be abused? -- 100: What support groups, books, and Web sites can I go to for help? -- Resources -- Bibliography -- Glossary -- Index
Includes bibliographical references and index
13
Keywords: Schizophrenia -- Miscellanea; Schizophrenia -- Popular works